Virtual black holes, remnants and the information paradox. (21st January 2015) - Calmet, Xavier
Abstract: We revisit the question of the contributions of Planckian quantum black holes in general and of remnants in particular to low-energy physics observables. As long as quantum gravity preserves the symmetries of the low-energy effective field theory, we find that the bounds on the number of quantum black holes or remnants are very weak. Typically, we rule out using data on the anomalous magnetic moment of the muon that there are more than 10 32 quantum black holes coupled to the standard model particles gravitationally. Remnants thus remain a viable option as a solution to the information paradox of black holes.